Mathematical Interpretation of the Geblek Renteng Batik Theme: Exploring Geometric Transformations - Siswanto, Deny Hadi (The Indonesian Institute of Science and Technology Research, 2025)
This research seeks to explore the connection between ethnomathematics and Geblek Renteng Batik, a unique cultural symbol of Kulon Progo. UNESCO's recognition of Batik as part of Human Heritage underscores its cultural significance. This acknowledgment offers the potential to use Batik as an alternative educational tool in mathematics, enhancing the understanding of mathematical concepts in everyday contexts. The study utilizes a qualitative descriptive methodology within an ethnographic framework. Data collection was carried out through interviews, observation, and documentation and the research instrument was a questionnaire. Data validation is performed through qualitative descriptive analysis. The study's results indicate that Batik Geblek Renteng themes incorporate mathematical concepts such as triangles, polygons, translations, reflections, rotations, and dilations. The integration of these mathematical concepts with the cultural aspects of Batik Geblek Renteng aims to foster a culturally enriched approach to learning mathematics.